Influence of Braking Strategies for Electric Trike Energy Consumption - Islameka, Metha; Kusuma, Christopher; Budiman, Bentang (Unijourn Publisher, 2020)
This research aims to investigate the effect of applying braking strategies to the energy consumption of electric trike (e-trike). E-trike is a three-wheeled vehicle that is designed for goods delivery. A simulation is carried out to find the specific electric energy consumption in terms of km/kWh. The simulation is conducted by developing an energy consumption model using Matlab/Simulink software. The input data used in the simulation is obtained from the e-trike specification designed by Institut Teknologi Bandung (ITB) researchers. The output is the battery State of Charge (SOC) and energy required for the Worldwide Harmonized Light Vehicle Test Procedure (WLTP) driving cycle. Four different braking strategies are implemented in the simulation, namely full mechanical braking, serial regenerative braking, parallel regenerative braking, and modified braking strategies. The simulation results show that by applying the modified braking strategy, greater savings of energy can be achieved. Full mechanical braking strategy can achieve energy savings of 19.2 km/kWh whereas the modified braking strategy generates 20 km/kWh. These results indicate that the application of modified braking strategies can significantly increase the e-trike mileage.